Development of a feasible and acceptable digital prehabilitation pathway to improve elective surgical outcomes - Linedale, Ecushla C.; Bills, Eleanor; Dimopoulos, Anastasia; Yeoh, Jackie; Nolan, Mandy; Hume, Vicki; Coles, Sharyn; Andrews, Jane M. (Frontiers in Digital Health, 2023)
Objective(s) To codesign and assess the feasibility, acceptability, and appropriateness of a hospital-initiated, community delivered approach to health optimization (prehab) prior to planned surgery. Design Participatory codesign combined with a prospective, observational cohort study (April–July 2022). Setting A large metropolitan tertiary referral service with 2 participating hospitals. Participants All people referred for orthopaedic assessment for joint replacement surgery (hip or knee) triaged as category 2 or 3. Exclusions: category 1; no mobile number. Response rate 80%. Intervention My PreHab Program is a digitally enabled pathway that screens participants for modifiable risk factors for post-operative complications and provides tailored information to enable health optimization prior to surgery with the help of their regular doctor. Outcome measures Acceptability, feasibility, appropriateness, and engagement with the program. Results 36/45 (80%) registered for the program (ages 45–85 yrs.), completed the health-screening survey and had ≥1 modifiable risk factor. Eighteen responded to the consumer experience questionnaire: 11 had already seen or scheduled an appointment with their General Practitioner and 5 planned to. 10 had commenced prehab and, 7 planned to. Half indicated they were likely (n = 7) or very likely (n = 2) to recommend My PreHab Program to others. The My PreHab Program scored an average 3.4 (SD 0.78) for acceptability, 3.5 (SD 0.62) for appropriateness, and 3.6 (SD 0.61) for feasibility, out of a score of 5. Conclusion(s) This digitally delivered intervention is acceptable, appropriate, and feasible to support a hospital-initiated, community-based prehab program.